Questions and answers for physicians : a medieval Arabic study manual. - Leiser, G. (Sir Henry Wellcome Asian series ;, 2004)
This work is a study guide for students of medicine prepared by Abd al-Aziz al-Sulami who was chief of medicine to the Ayyubid sultan in Cairo between 596/1200 and 604/1208. Each chapter contains 20 questions on the respective subject with the answer to each question.